Morphological Study of The Meaning of Wazan Af'ala and Taf'il in The Qur'an Juz 30 - Abdul Kosim; Julia Rizkiani; Fennie Rufaidah S; Irham Maulana (Program Pascasarjana UIN Sumatera Utara, 2023)
In helping to reveal the deep meaning of the verses of the Qur'an so as to enrich understanding and add insight through the structure and root words in the verses of the Qur'an that are related to historical and spiritual contexts, morphological analysis has been important significance. By analyzing examples of Al-Qur'an verses, this study shows the effect of using wazan in expressions in Arabic. morphology or look at the structure of words. This type of library research is used in a qualitative descriptive manner with data in the form of verses of the Qur'an Juz 30 printed by Mujamma' Malik Fahdi Lithoba'ah Al-mushaf Alsyarif Madinah. The results of the study revealed that there were 24 words with wazan af'ala and taf'il in the Qur'an juz 30 which explained the change from fi'il mujarrad to fi'il mazid giving a different meaning to the meaning of the verses of the Koran. Dalam membantu mengungkapkan makna mendalam dari ayat-ayat Al-Qur'an sehingga memperkaya pemahaman dan penambahan wawasan melalui struktur dan akar kata dalam ayat-ayat Al-Qur'an yang berhubungan dengan konteks historis dan spritual, analisis morfologi memiliki signifikansi yang penting. Dengan menganalisis contoh ayat Al-Qur'an, penelitian ini menunjukkan pengaruh penggunaan wazan dalam ekspresi dalam bahasa Arab Studi ini bertujuan untuk memberi deskripsi mengenai ayat-ayat Al-Qur'an yang berwazan af'ala dan berwazan taf'il serta maknanya ditinjau secara morfologi atau melihat struktur kata. Jenis penelitian kepustakaan digunakan secara deskriptif kualitatif dengan data berupa ayat Al-Qur'an Juz 30 cetakan Mujamma' Malik Fahdi Lithoba'ah Al-mushaf Alsyarif Madinah. Hasil penelitian mengungkapkan terdapat sebanyak 24 kata yang berwazan af'ala dan taf'il dalam Al-Qur'an juz 30 yang menjelaskan berubahnya fi'il mujarrad menjadi fi'il mazid memberikan makna yang berbeda pada arti ayat Al-Qur'an. Kata Kunci: Morfologi, Wazan af'ala dan taf'il, Al-Qur'an Juz 30